PENGARUH KONSENTRASI ASAP CAIR DAN LAMA PENYIMPANAN TERHADAP DAYA IKAT AIR DAN DAYA PUTUS DAGING - Bahtiar Bahtiar; Effendi Abustam (Jurnal Ilmu dan Industri Peternakan, 2014)
ABSTRACT. This study was conducted in September-Oktober 2013. Locations research laboratory housed in Livestock Products Technology, Faculty of Animal Husbandry, Hasanuddin University, Makassar . This study aims to determine the effect of liquid smoke concentration and storage time on the quality of beef muscle bali longissimus Dorsi (LD). The research method is based on completely randomized design (CRD) with a general pattern that is 4 x 4 with 3 replications, Composition of treatment as follows: The first factor is the concentration of liquid smoke to the A1 (0 % by weight of liquid smoke meat), A2 (10 % smoke heavy liquid from the meat), A3 (20 % by weight of liquid smoke meat), A4 (30 % by weight of liquid smoke meat). Factor II is the long storage with B1 (0 weeks), B2 (1 week), B3 (2 weeks) and B4 (3 weeks). Data were analyzed by analysis of variance using a completely randomized design (CRD) consisting of 6 parameters of meat quality testing using the Least Significant Difference Test (BNT) . Based on the results of analysis of variance and showed that the concentration of liquid smoke significantly affect the value of the Power Disconnect Meat (DPD), whereas storage time significantly affected the water holding capacity (DIA).